IDENTIFICATION AND PREVALENCE OF PLANT-PARASITIC NEMATODES ASSOCIATED WITH CORN IN SOUTHERN CEBU - Tolentin, Rocel M; Quisado, Catherine; Pascual, Maria Lima D (Journal of Agriculture and Technology Management, 2022)
Plant-parasitic nematodes are reported to be associated with corn and are one of the limiting factors for yield reduction. A survey was conducted to identify genera of plant-parasitic nematode associated with corn and its prevalence in Southern Cebu, Philippines. Root and soil samples were collected from five corn growing municipalities of Cebu (Santander, Argao, Badian, Alegria and Barili, Cebu). Nematodes from roots and soil samples were extracted following standard methods and were identified to genus level based on morphology. A total of eight (8) plant-parasitic nematode genera ( Criconemella, Helicotylenchus ,  Hoplolaimus ,  Meloidogyne ,  Paratylenchus ,   Pratylenchus , Tylenchorhynchus , and Tylenchus ) belonging to seven (7) different families were identified. Among these identified genera, Pratylenchus were the most abundant in corn roots and Helicotylenchus in soil rhizosphere. Both genera were found to have high frequency of occurrence and abundance in different corn fields surveyed. The other genera were less prevalent as manifested by their relatively low abundance and frequency of occurrence. This information may raise awareness of farmers on prevalent plant-parasitic nematodes in their area and guide in undertaking appropriate management actions.